2020
DOI: 10.1186/s12894-020-00644-z
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response syndrome in patients with acute obstructive upper tract urinary stone: a risk factor for urgent renal drainage and revisit to the emergency department

Abstract: Background In patients seen in the emergency department (ED) with acute stone obstruction many risk factors that indicate need for urgent renal drainage are known. However, in patients discharged from ED without renal drainage factors that can minimize revisit to the emergency department are not fully identified. We evaluated SIRS (systemic inflammatory response syndrome) as a risk factor for urgent renal drainage and revisit to the ED in patients with acute stone colic during their ED visit. Methods Retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our case is an example of how the implementation of point-of-care ultrasound can help differentiate between simple urinary tract infections versus complicated causes of pyelonephritis, more specifically the presence of hydronephrosis that might require urologic intervention if the patient has evidence of sepsis and genitourinary obstruction. In this young patient, with no prior history of urinary tract infections, ultrasound helped us by identifying a condition that if discharged with typical treatment for urinary tract infection could have caused the patient to return with a worsening condition due to the presence of a genitourinary tract obstruction and systemic inflammation [8]. As emergency medicine continues to move toward metrics such as door-to-antibiotic time and door-to-disposition time, the use of a tool that helps the clinician quickly rule out or rule in a diagnosis can be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Our case is an example of how the implementation of point-of-care ultrasound can help differentiate between simple urinary tract infections versus complicated causes of pyelonephritis, more specifically the presence of hydronephrosis that might require urologic intervention if the patient has evidence of sepsis and genitourinary obstruction. In this young patient, with no prior history of urinary tract infections, ultrasound helped us by identifying a condition that if discharged with typical treatment for urinary tract infection could have caused the patient to return with a worsening condition due to the presence of a genitourinary tract obstruction and systemic inflammation [8]. As emergency medicine continues to move toward metrics such as door-to-antibiotic time and door-to-disposition time, the use of a tool that helps the clinician quickly rule out or rule in a diagnosis can be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Нами были оценены факторы риска развития осложнённой СВО у пациентов с МКБ. В целом, уровень с осложнённым течением соответствовал или был выше данных, приведённых в литературе [9]. Относительно высокая встречаемость осложнённого течения МКБ, составляющих изначально сложную когорту пациентов типична для специализированных центров по лечению урологических заболеваний.…”
Section: Discussionunclassified
“…Last but not least, it has been demonstrated that presence of SIRS in obstructive urolithiasis patients was associated with increased risk for revisits to the emergency department 5 . A timely renal drainage according to Sepsis-2 de nition may contribute to decrease the probability of relapse caused by persistent obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we require objective biomarkers to serve as indicators of response to the therapeutic intervention. A large armamentarium of serum sepsis biomarkers has been reported over the past years 4 , however, a majority of tests are experimental, costly and not commonly available in the emergent department in a timely manner 5 . Leukocytosis still plays a vital role in predicting the risk of sepsis and triggering surgical decompression of OUs 6 .…”
Section: Introductionmentioning
confidence: 99%